Essentials of gerontological nursing - Wallace, Meredith (Springer, 2007)
Essentials of Gerontological Nursing presents the best practices needed to care for older adults. Its brief, yet comprehensive, grasp of issues in elder care is a refreshing addition to the current literature, which is more commonly focused on theory than on clinical practice. Designed primarily for students in gerontological nursing courses in BSN and graduate programs, the book provides: Essential clinical information and "best practices" needed to care for older adults Current research and new patient approaches in gerontological nursing Overviews of rarely discussed issues, such as elder abuse, cultural considerations, and restraint alternatives Clinical specifications and practical applications Content designed to fit into a one-semester course Essentials of Gerontological Nursing is everything the nursing student needs to know when caring for older adults